(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the evolution of money velocity in Libya between 2008 and 2022, focusing on its theoretical foundations and the key macroeconomic determinants influencing its fluctuations The research applies both descriptive analysis of time-series data and econometric modeling using Ordinary Least Squares (OLS) regression. Variables considered include GDP, money supply (M1), oil revenues, inflation, legal reserve ratio, and extraordinary conditions (wars, pandemics). The results reveal that money velocity in Libya was highly unstable, with sharp declines during crisis years (2011 due to armed conflict and 2020 due to the COVID-19 pandemic). Econometric analysis shows that oil revenues exert a significant positive effect on money velocity, while inflation and the legal reserve ratio had weak and statistically insignificant impacts. Extraordinary conditions had a strong negative influence, reflecting increased liquidity hoarding during crises. The study concludes that the weak role of monetary institutions, particularly the Central Bank of Libya, and the limited effectiveness of traditional monetary policy tools contributed to economic instability. It recommends strengthening monetary policy instruments, enhancing institutional capacity, and improving policy responsiveness to better manage fluctuations in money velocity and stabilize the Libyan economy